Implementasi Model Pembelajaran STAD untuk Meningkatkan Aktivitas dan Hasil Belajar IPA Materi Sistem Gerak pada Manusia - Dede Kusnandar (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2021)
The research was motivated by the low activity and learning outcomes of science. This study aims to improve learning outcomes and learning activities of class VIII-B MTs Legokjawa Pangandaran Semester I 2018/2019 academic year through the implementation of the STAD learning model. This research was carried out in two cycles, each cycle consisting of two meetings. The stages of each cycle consist of the following stages: Planning, Implementation, Observation, and Reflection. The data collection of this research was done by observation and written test. The results of the study concluded that the implementation of the STAD cooperative learning model implementation could improve student learning outcomes in the Science Subjects of the Human Movement System material. This is supported by research data showing an increase in class average scores and an increase in the percentage of completeness in science learning outcomes tests. At the time of pre-study, the percentage of student completeness was only 39.29% with an average grade of 58.14, in the first cycle with the implementation of the STAD Cooperative learning model the percentage of mastery learning outcomes increased to 64.29% with an average score of 64.71. In the second cycle, the completeness of learning outcomes reached 92.86% with an average grade of 76.11. The implementation of the STAD Cooperative learning model can also increase the learning activities of class VIII-A students of MTsN 2 Pangandaran in the first semester of the 2018/2019 academic year, in the first cycle student learning activities are 82.22% and increase to 84.29% in the second cycle.